Indomethacin: Effect of Diffusionless Crystal Growth on Thermal Stability during Long-Term Storage - Svoboda, Roman; Koutná, Nicola; Košťálová, Daniela; Krbal, Miloš; Komersová, Alena (Molecules (Basel, Switzerland), 2023)
Differential scanning calorimetry and Raman spectroscopy were used to study the nonisothermal and isothermal crystallization behavior of amorphous indomethacin powders (with particle sizes ranging from 50 to 1000 µm) and their dependence on long-term storage conditions, either 0-100 days stored freely at laboratory ambient temperatures and humidity or placed in a desiccator at 10 °C. Whereas the γ-form polymorph always dominated, the accelerated formation of the α-form was observed in situations of heightened mobility (higher temperature and heating rate), increased amounts of mechanically induced defects, and prolonged free-surface nucleation. A complex crystallization behavior with two separated crystal growth modes (originating from either the mechanical defects or the free surface) was identified both isothermally and nonisothermally. The diffusionless glass-crystal (GC) crystal growth was found to proceed during the long-term storage at 10 °C and zero humidity, at the rate of ~100 µm of the γ-form surface crystalline layer being formed in 100 days. Storage at the laboratory temperature (still below the glass transition temperature) and humidity led only to a negligible/nondetectable GC growth for the fine indomethacin powders (particle size below ~150 µm), indicating a marked suppression of GC growth by the high density of mechanical defects under these conditions. The freely stored bulk material with no mechanical damage and a smooth surface exhibited zero traces of GC growth (as confirmed by microscopy) after >150 days of storage. The accuracy of the kinetic predictions of the indomethacin crystallization behavior was rather poor due to the combined influences of the mechanical defects, competing nucleation, and crystal growth processes of the two polymorphic phases as well as the GC growth complex dependence on the storage conditions within the vicinity of the glass transition temperature. Performing paired isothermal and nonisothermal kinetic measurements is thus highly recommended in macroscopic crystallization studies of drugs with similarly complicated crystal growth behaviors.
Keywords: Transition Temperature; kinetic prediction; storage; indomethacin; tranzitní teplota; crystallization; Temperature; amorphous indomethacin; Indomethacin; velikost částic; Crystallization; krystalizace; particle size; Calorimetry, Differential Scanning; teplota; diferenciální skenovací kalorimetrie; Particle Size